NONVERBAL MEANS OF COMMUNICATION AND SIGNS - Shamsutdinova Nazokat Alisherovna, (Ustozlar uchun, 2025)
This article is devoted to non-verbal communication and its various means and forms. The article tells about the importance and features of non-verbal communication and its differences from verbal communication and the degree of study of non-verbal communication. Signs and symbols are common forms of non-verbal communication that exist and are widely used to convey information.